2019
DOI: 10.1177/1358863x19872547
|View full text |Cite
|
Sign up to set email alerts
|

One-day, sequential carotid artery stenting followed by cardiac surgery in patients with severe carotid and cardiac disease

Abstract: Optimal management of patients with internal carotid artery (ICA) stenosis concurrent with severe cardiac disease remains undefined. The aim of this study is to evaluate the safety and feasibility of the one-day, sequential approach by carotid artery stenting (CAS) immediately followed by cardiac surgery. The study included 70 consecutive patients with symptomatic > 50% or ⩾ 80% asymptomatic ICA stenosis coexisting with severe coronary/valve disease, who underwent one-day, sequential CAS + cardiac surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In addition, a number of studies have shown that phased CAS and CABG procedures may be effective and risk-free (26,27). Individuals who have significant atherosclerotic disease and who come in an unstable state and need an urgent OHS may benefit from a less intrusive therapy, such as CAS, to address carotid artery stenosis, which may enhance the risk of stroke for OHS patients (28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of studies have shown that phased CAS and CABG procedures may be effective and risk-free (26,27). Individuals who have significant atherosclerotic disease and who come in an unstable state and need an urgent OHS may benefit from a less intrusive therapy, such as CAS, to address carotid artery stenosis, which may enhance the risk of stroke for OHS patients (28).…”
Section: Discussionmentioning
confidence: 99%
“…This was a prospective study in consecutive patients referred for potential carotid revascularization to a tertiary vascular centre performing high-volume carotid revas-cularization by means of CEA, CAS, and TCAR in patients with indications established by the multispecialty Neuro-Vascular Team and a final decision on the treatment modality incorporating the patient's informed opinion [29][30][31][32][33][34][35][36][37][38]. Referral stenosis severity had to be at least "50%" according to the modality and measurement method used by the referring centre.…”
Section: Methodsmentioning
confidence: 99%
“…Prospective data collection involved all consecutive patients with AIS receiving cerebral and vascular imaging in 2 collaborating centers with acute stroke neurology. Study Center 1 is a high-volume major tertiary 24/7 cardiovascular center with carotid artery stenting (CAS) expertise with a case load of 350-400 CAS procedures per year [26][27][28] and MT service under World Federation for Stroke Treatment (WIST) certification and supervision (Level-2 stroke center -Thrombectomy-Capable Stroke Center, TCSC) [24,29]. In addition, vascular surgery treatments (including carotid endarterectomy of »200 cases per year) are performed [26][27][28].…”
Section: Study Centersmentioning
confidence: 99%
“…Study Center 1 is a high-volume major tertiary 24/7 cardiovascular center with carotid artery stenting (CAS) expertise with a case load of 350-400 CAS procedures per year [26][27][28] and MT service under World Federation for Stroke Treatment (WIST) certification and supervision (Level-2 stroke center -Thrombectomy-Capable Stroke Center, TCSC) [24,29]. In addition, vascular surgery treatments (including carotid endarterectomy of »200 cases per year) are performed [26][27][28]. A multispecialty local Stroke Endovascular Mechanical Reperfusion Team with interventional cardiology and angiology, stroke neurology, radiology, and anesthesia is operational within the Level-2 WIST stroke center framework [24,29].…”
Section: Study Centersmentioning
confidence: 99%